2016
DOI: 10.1021/acs.langmuir.5b04633
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS Study of Sr sorption to Illite, Goethite, Chlorite, and Mixed Sediment under Hyperalkaline Conditions

Abstract: Strontium is an important contaminant radionuclide at many former nuclear sites. This paper investigates the effect of changing pH and ionic strength on the sorption of Sr to a range of common soil minerals. Specifically it focuses on the sorption of Sr onto illite, chlorite, goethite, and a mixed sediment. The interplay between ionic strength and pH was determined by varying the background ionic strength of the system using both NaCl (for a constant pH) and NaOH (to also vary pH). Under conditions of moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 48 publications
(87 reference statements)
7
55
1
Order By: Relevance
“…During both approaches, FEFF6 53 was used to calculate the theoretical (initial) Sr and Cs scattering paths by developing complexation models using the crystallographic information files for anatase, 54 kaolinite 55 and illite, 56 based on previous analytical and molecular dynamics results. 15,20,21,27,31,35,36…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%
See 3 more Smart Citations
“…During both approaches, FEFF6 53 was used to calculate the theoretical (initial) Sr and Cs scattering paths by developing complexation models using the crystallographic information files for anatase, 54 kaolinite 55 and illite, 56 based on previous analytical and molecular dynamics results. 15,20,21,27,31,35,36…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%
“…[8][9][10][11][12][13] Transport of fission products like caesium(Cs) and strontium (Sr) through the environment is heavily impacted by the soil mineralogy (including clay minerals and metal oxides in the soils at the Little Forest Legacy Site 3,4,7 ), their surface speciation and complexation with organic matter. 10,11,[14][15][16][17][18][19] Previous studies have identified multiple surface complexes for Sr and Cs complexed with mineral phases present within clayey soils using X-ray absorption spectroscopy and molecular dynamics techniques. Sr has been shown to complex with kaolinite through the formation of hydrated (outer-sphere) surface complexes at elevated concentration and inner-sphere complexes at lower concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of pH on the Sr and Cs ions adsorption capacities by the Z-S1 was examined in the pH range of 2 -10. The form of Cs and Sr species in aqueous solutions exist in the form of Sr 2+ and Cs + at the pH range of 2-12 [27,28]. As seen in Fig.…”
Section: Effect Of Phmentioning
confidence: 88%